We can generate the terms of a sequence by using the rule for first order difference equations.

## First Order Difference Equation

A reminder of what a general first order difference equation looks like: $t_{n+1}=t_n+b$ $t_1=a$

### Example 1

Find the first four terms of the sequence defined by the first order difference equation: $t_n=2t_{n-1}+4$ $t_1=8$

We know that the starting term ( $t_1$) so we can generate the next term ( $t_2$) by completing the equation. $t_2=2t_1+4$ $t_2=2\times 8+4$ $t_2=20$

Now use $t_2$ to calculate $t_3$ $t_3=2t_2+4$ $t_3=2\times 20+4$ $t_3=44$

Now use $t_3$ to find $t_4$ $t_4=2t_3+4$ $t_4=2\times 44+4$ $t_4=92$

The first four terms are 8, 20, 44 and 92.

### Example 2

A sequence is defined by the first order difference equation: $t_{n+1}=4t_n+6$ $n=1, 2, 3, ...$

If $t_5=1,278$, what is the third term?

We need to calculate the previous term so transpose the equation to make $t_n$ the subject. $t_n=\frac {t_{n+1}-6}{4}$

Now, use $t_5$ to find $t_4$ using the transposed equation. $t_4=\frac {t_5-6}{4}$ $t_4=\frac {1,278-6}{4}$ $t_4=318$

Now we can use $t_4$ to find $t_3$. $t_3=\frac {t_4-6}{4}$ $t_3=\frac {318-6}{4}$ $t_3=78$

The third term is 78.